Find answers, ask questions, and connect with our
community around the world.

Activity Discussion Math Math

Tagged: 

  • Chammi

    Member
    July 8, 2024 at 5:54 pm
    Helpful
    Up
    0
    Down
    Not Helpful
    ::

    To simplify the expression 2(x + 4) – 3(x – 2), we can apply the distributive property and then combine like terms.

    First, let’s distribute the 2 and the 3:

    2(x + 4) = 2x + 8

    3(x – 2) = 3x – 6

    Now we can substitute these expressions back into the original equation:

    2(x + 4) – 3(x – 2) = (2x + 8) – (3x – 6)

    Next, distribute the negative sign to the terms inside the parentheses:

    = 2x + 8 – 3x + 6

    Finally, combine like terms:

    = (2x – 3x) + (8 + 6)

    = -x + 14

    Therefore, the simplified expression is -x + 14.

For Worksheets & PrintablesJoin Now
+